CBCT Management of Previously Treated Mandibular Incisor with Extensive Internal Root Resorption: A Case Report - Ruth Pérez Alfayate; Ana Suarez; Juan Algar Pinilla (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
This case report describes a central mandibular incisor's retreatment. Follow-up with perforating internal root resorption managed using a reciprocating file and obturated with down-pack and backfill technique, a surgical approach to seal the perforation. The medical history was non-contributory, and he had a history of traumatic injury resolved by a general dentist one year before. Tooth (4.1) presented pain and, after inspection and exploration, the clinical diagnosis was established as a previously-treated tooth with apical periodontitis. During periodic clinical and radiographic follow-up, the patient remained symptom-free, meeting functional expectations after eight years. Understanding the pathology and knowing the techniques to manage it could help recover the function of teeth considered lost.